Evaluation of Rural Electrification Programme Volume II - Planning Commission (Planning Commission, 1983)
The present Report is in continuation of Volume I brought out in 1982 which covered organisation, growth and coverage of Rural Electrification Programme. Volume II of the report reflects the views of the "beneficiaries" as well as "non-beneficiaries" of various categories, selected for the purpose, on different aspects of rural electrification and also attempts to study the impact of the programme.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India